Releasing the imagination : essays on education, the arts, and social change - Greene, Maxine (San Francisco : Jossey-Bass Publishers, 1995)
This volume] defines the role of imagination in general education, arts education, aesthetics, literature, and the social and multicultural context. [In the volume], the author argues for schools to be restructured as places where students reach out for meanings and where the previously silenced or unheard may have a voice. She invites readers to develop processes to enhance and cultivate their own visions through the application of imagination and the arts. Releasing the Imagination should be required reading for all educators, particularly those in teacher education, and for general and academic readers.-http://www.loc.gov/catdir.
Includes bibliographical references and index.
Keywords: Education -- Aims and objectives -- United States; Education -- Social aspects -- United States; Educational change -- United States; Arts -- Study and teaching -- United States